Microbial transformation of Clarias gariepinus oil by psuedomonas aeruginosa - Omar, Muhammad Nor; Shaban, Norhayati; Bakar, Latifah Munirah; Zuberdi, Ahmad Muzammil (Oriental Scientific Publishing Co., 2014)
Biotransformation of fatty acid from Malaysian catfish, Clarias gariepinus oil was carried out using Pseudomonas aeruginosa. The lipid from freeze-dried catfish flesh was extracted using a modified Folch method with chloroform-methanol mixture as an extracting solvent. The crude lipid substrate was added to P. aeruginosa culture and incubated for 4 days. After conversion, the products were analyzed by using GC-MS instrument. The result showed that 7,10-dihydroxy-8(E)-octadecenoic acid (DHOD) were abundantly found in the product. The hydroxyl derivative increased while fatty acid contents decreased after biotransformation process. It can be concluded that the bacterial cells had transformed the fatty acids to yield hydroxyl metabolite which can be utilized as starting materials for the bioconversion to pharmaceutical materials.